Música como escrita e som: o desafio de representar e de recuperar - Saluzi, Lorrane de Souza (2021)
This work proposes to discuss the music document and its written and sound representation. The general objective is to investigate music as written and sound in the representation and retrieval of information. As specific objectives, it aims to address some of the main points in the history of music and identify if there are patterns of representation and recovery in music. Descriptive research, with a qualitative and quantitative approach, through observation, collection and analysis of data on music databases, available in a virtual environment of Brazilian institutions and an international specialized scientific production. The results identified descriptive fields for technical processing in music in Brazilian institutions, signaling the most used terms in scientific publications in the last two decades, leveled for the evolution of the theme music in information retrieval. Among the institutions studied, the one that stands out in relation to the representation, recovery and availability of the National Library Foundation's virtual collection. We conclude that Information Science, when observing music as a document, has theoretical potential for deepening patterns and not improving the representation and recovery of music as writing and sound.